(untitled) (Sciental Journal of Education Humanities and Social Sciences, 2026)
This study examines the pragmatic functions and linguocultural manifestations of temporal deixis in English and Uzbek literary discourse through a corpus-based comparative analysis. Drawing on a corpus of 20 literary texts (10 English, 10 Uzbek) from the 20th and 21st centuries, we analyzed 847 instances of temporal deictic expressions. The analysis reveals that while temporal deixis serves universal pragmatic functions—including narrative anchoring, perspective-shifting, and discourse structuring—its realization differs significantly across the two languages. English temporal deixis exhibits predominantly referential and sequential functions, reflecting a linear time conceptualization, whereas Uzbek temporal deixis demonstrates stronger evaluative and collective-memory orientations, reflecting cyclical and tradition-centered temporality. The findings contribute to cross-linguistic pragmatics, translation studies, and linguocultural semantics.